2022
DOI: 10.21037/atm-22-3339
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of integrin β2 improves migration and engraftment of adipose-derived stem cells and augments angiogenesis in myocardial infarction

Abstract: Background: Adipose-derived stem cells (ASCs) hold a great promise for myocardial infarction, but therapeutic efficacy appears to be limited by their poor survival and engraftment. Integrins are transmembrane proteins known to regulate the biological behaviors of stem cells. Integrin β 2 (ITGB2) specifically binds to intercellular cell adhesion molecule-1 (ICAM-1), which is upregulated in infarcted myocardium. ASCs typically express an insufficient amount of ITGB2, and this may limit their homing and engraftme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In recent years, it has been found that ITGB2 mediates a metabolic switch in cancerassociated fibroblasts, promoting oral squamous cell carcinoma proliferation 18 . In a study on myocardial infarction, overexpression of ITGB2 increased the migration and improved the engraftment of adipose-derived stem cells and augmented angiogenesis 19 . Sequencing of carotid atherosclerosis samples showed that ITGB2 was a key gene 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that ITGB2 mediates a metabolic switch in cancerassociated fibroblasts, promoting oral squamous cell carcinoma proliferation 18 . In a study on myocardial infarction, overexpression of ITGB2 increased the migration and improved the engraftment of adipose-derived stem cells and augmented angiogenesis 19 . Sequencing of carotid atherosclerosis samples showed that ITGB2 was a key gene 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Kdr in MCODE-5 drives meningeal vascular regeneration during head injury ( 37 ). In KEGG analysis of Itgb2 together with the proteins in PPI of MCODE, it was demonstrated that endothelial progenitor cell transplantation can promote neovascularization in ischemic tissues through ITGB2/IACM-1 interaction ( 31 , 38 ). And we speculated this might regulate the neovascularization process in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs restored the expression of integrin β 2 that specifically blocks ICAM-1 and reduces macrophage accumulation in infarcted myocardium, increasing cell viability, proliferation, and migration [67]. In addition, ASC-derived exosomes mitigated MI-induced cardiac damage by promoting macrophage M2 polarization by restoring the expression of the sphingosine-1-phosphate receptor 1 (S1PR1) [68,69].…”
Section: Adipose-derived Stem Cells Preserve Heart Function In Precli...mentioning
confidence: 99%